Особливості процедури внесення змін до розділів I, III, XIII Конституції України - Рудик, Петро Андрійович (My University, 2013)
В статті відповідно до Конституції та найновіших законів України увага концентрується на розкритті особливостей процедури внесення змін до розділів I, III, XIII Конституції України та появі у законодавстві нашої країни нових положень і видів всеукраїнських конституційних референдумів. The author of the article has concentrated the attention on a procedure of amending changes into the Ist, IIIrd, and XIIIth Sections of Constitution of Ukraine in accordance with the Constitution and other newest laws. There was also revealed the apparition of new statements and forms for all-Ukrainian constitutional referendums.
Keywords: закон України; внесення змін; Конституція України; laws of Ukraine; amendment procedures; Constitution of Ukraine; кафедра економіки і права